Diagnostic outcome of contrast videofluoroscopic swallowing studies in 216 dysphagic dogs. Issue 4 (23rd March 2017) - Pollard, Rachel E.; Marks, Stanley L.; Cheney, Diane M.; Bonadio, Cecily M.
Abstract: Determining the anatomic and functional origin for dysphagia is critical for development of an appropriate therapeutic plan and determination of the prognosis. The purpose of this retrospective study was to report the quantitative and qualitative outcome of contrast videofluoroscopic swallowing studies in a large cohort of dysphagic dogs presenting to a tertiary veterinary care hospital. The videofluoroscopic swallowing studies were reviewed to generate values for pharyngeal constriction ratio, timing of swallowing events (maximum pharyngeal contraction, opening of upper esophageal sphincter, closing of upper esophageal sphincter, and reopening of epiglottis), type of esophageal peristalsis generated, and esophageal transit time. One or more anatomic locations for origin of dysphagia were assigned (pharyngeal, cricopharyngeal, esophageal (primary motility disorder), other esophageal (stricture, vascular ring anomaly, mass), lower esophageal sphincter/hiatus. Sixty‐one of 216 studies (28%) were deemed unremarkable. Twenty‐seven of 216 dogs (13%) had pharyngeal dysphagia, 17/216 dogs (8%) had cricopharyngeal dysphagia, 98/216 dogs (45%) had dysphagia secondary to esophageal dysmotility, 19/216 dogs (9%) had dysphagia secondary to focal esophageal disorders, and 97/216 dogs (45%) had dysphagia of lower esophageal sphincter/hiatus origin. Multiple abnormalities were present in 82/216 (38%) dogs. Elevated pharyngeal constriction ratio was associated with pharyngeal, cricopharyngeal, and esophageal motility disorders, delayed upper esophageal sphincter opening was associated with cricopharyngeal disorders, a lower percentage of primary esophageal peristaltic waves was associated with cricopharyngeal, pharyngeal, or primary esophageal motility disorders. In conclusion, videofluoroscopic swallowing studies was pivotal in the diagnosis of dysphagia with 155/216 (72%) dogs receiving a final diagnosis.